ANALISIS YURIDIS AKIBAT HUKUM ATAS PERKAWINAN CAMPURAN BEDA NEGARA YANG TIDAK DIDAFTARKAN DI KANTOR CATATAN SIPIL NEGARA REPUBLIK INDONESIA (STUDI PENELITIAN DI KANTOR CATATAN SIPIL PEMERINTAH KOTA BATAM) - Laily Washliati; Titik Aminah; Agus Triyana (Ensiklopedia of Journal, 2023)
Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage states that: A marriage which is carried out outside Indonesia with two Indonesian citizens or an Indonesian citizen with a foreign national is legal if it is carried out according to the laws in force in the country. the country where the marriage was held for Indonesian citizens. However, in reality many mixed marriage couples from different countries do not register their marriages with the Civil Registry Office. The purpose of writing this journal is to find out the legal arrangements for mixed marriages of different countries that are not registered at the Civil Registry Office, and to find out the legal consequences, obstacles and efforts to implement mixed marriages of different countries that are not registered with the Civil Registry Office. The results of the study indicate that legal arrangements for mixed marriages of different countries that are not registered at the Civil Registry Office, namely mixed marriages have an obligation to register them at the Civil Registry Office to become the strongest evidence in determining a person's legal position and maintaining the rights of husband and wife in a marriage. marital bond. This obligation is shown from the existence of criminal sanctions regulated in Article 61 of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage. The legal consequences of implementing mixed marriages in different countries that are not registered with the Civil Registry Office are legal consequences for the parties to mixed marriages, and legal consequences for children born from mixed marriages. Factors constraining the implementation of mixed marriages in different countries that are not registered are the difficulty in managing the legality in the implementation of mixed marriages, and the low legal awareness of the community towards the requirements that must be met in the implementation of mixed marriages in different countries. And efforts that can be made to overcome these obstacles are the need for legal assistance for mixed marriage couples, and the need to increase legal socialization for mixed marriages.